Comparison of Lecture and Video Methods in Increasing Caregiver Knowledge in Treating Clients Halusination - Bambang Eryanto; Taty Hernawaty; Shelly Iskandar (Universitas Padjadjaran, 2018)
Efforts to improve caregiver’s knowledge on hallucination is by providing an education the caregivers. Enhancing such knowledge can be carried out by different methods, include lecture and watching video methods. The purpose of the present research was to compare the effectiveness of lecture and watching video method in enhancing caregiver’s knowledge on hallucination. The research used a quasi-experiment method with a pretest and posttest group design, with the research sample was 60. The sampling technique used was a total sampling. The scores of caregiver’s knowledge were determined by a questionnaire of knowledge on hallucination that was self-developed by validity test (0.707) and reliability test (0.968). The data obtained was then tested by using Independent Sample T-test, Mann-Whitney test, and Wilcoxon test. The result of pretest of caregiver’s knowledge before the intervention showed that there was no difference between intervention and control group (p-value=0.624), while result of posttest of caregiver’s knowledge after the intervention showed that there was a significant difference between lecture group and video group (p-value=0.000). The research findings revealed that there was a significant increase in the scores of knowledge for both methods (p-value=0.000), but the increase of video group’s knowledge score was higher (4.23) than that of lecture group (2.57). The conclusion of the research was that wathing video method was more effective than lecture method in enhancing caregiver’s knowledge so that video can be used as an alternative method for mental health education.